(untitled) (SAARC Journal of Agriculture, 2021)
Botanicals are promising and attractive alternatives for pest management. In the present study, three botanical oils namely neem (Azadirachta indica), karanja (Pongamia pinnata) and mehogony (Swietenia mahagoni) were tested against the nymphs of Aphis craccivora Koch to evaluate the toxic and repellent effects under laboratory conditions (25 ± 5oC, 65-75% RH). Four concentrations (0.5, 1.0, 1.5, and 2.0%) along with control were maintained with distilled water and tween-20 was used as emulsifier. Leaf dipped method were used for insect bioassay. Insect mortality was recorded at 24, 48 and 72 hours after intervals while repellency was carried out at 2 hours after intervals upto 10th hours and the collected data were analyzed through MSTAT-C program. Results indicated that all the tested oils had toxic and repellent effects against the A. craccivora nymphs. Among the tested botanical oils, no significant difference was observed in terms of mortality over treatment time. But significant difference was noticed over level of concentrations exerted by the botanical oils. The average highest mortality (28.62%) was recorded by the application of mehogony oil whereas neem oil showed the lowest mortality (27.21%) against the A. craccivora and the mortality was directly proportional to the level of concentrations and hour after treatment (HAT). Probit analysis showed the lowest LD50 values of mehogony oil which revealed the highest toxic effect against the nymph of bean aphid. The highest repellent effect (77.33%) was found in mehogony oil (repellent class IV) among all the botanical oils applied. On the contrary, neem (57.33%) and karanja (55.00%) oils belonged to the same repellent class that is repellent class II. Although all the tested botanical oils evaluated showed toxic and repellent effects but mehogony oil performed as the best potent oil against the nymphs. We therefore suggested using the mehogony oil for the management of bean aphid. SAARC J. Agric., 19(1): 139-154 (2021)